Acute Carotid Stent Thrombosis: A Comprehensive Review. (October 2016) - Moulakakis, Konstantinos G.; Mylonas, Spyridon N.; Lazaris, Andreas; Tsivgoulis, Georgios; Kakisis, John; Sfyroeras, Giorgos S.; Antonopoulos, Constantine N.; Brountzos, Elias N.; Vasdekis, Spyridon N.
Acute carotid stent thrombosis (ACST) is a rare complication that can lead to dramatic and catastrophic consequences. A rapid diagnosis and prompt recanalization of the internal carotid artery are needed to minimize the ischemic insult and the reperfusion injury. We reviewed the current literature on this devastating complication of CAS with the intention of investigating the potential causative factors and to define the appropriate management. According to our study discontinuation of antiplatelet therapy, resistance to antiplatelet agents and inherent or acquired thrombotic disorders are the main causes of thrombosis. Technical intraprocedural parameters such as dissection, atheroma prolapse, kinking of the distal part of internal carotid artery and embolic protection device occlusion can also result in early carotid stent thrombosis. Rapid reperfusion ensures an improved neurological outcome and a better prognosis in the short and long term. Thrombolysis, mechanical thrombectomy or thromboaspiration in combination with drug or thrombolytic therapy, surgical therapy and re-angioplasty are treatment options that have been used with encouraging results. In conclusion, optimal perioperative antiplatelet treatment as well as technical considerations regarding the carotid artery stenting plays a determinant role.